Bodoči učitelji in poznavanje (ne)varnosti na spletu - Bratina, Tomaž (Revija za elementarno izobraževanje, 2012)
Future Teachers' Knowledge on Internet Safety (Risks). The modern way of delivering learning materials makes use of the advantages provided by ICT. ICT components which are related to the distribution of learning materials use computer networks or World Wide Web. Consequently, the teacher and the student alike need to possess certain knowledge which is not related to the subject matter itself. The knowledge in question regards a responsible and safe usage of online services. During their studies, students most commonly use online services through Learning Contents Management Systems, though this is not the only way. A responsible and safe usage of web applications is an essential part of one's digital competences, which comprise, among other things, also safe behaviour online. A common belief that knowing how to work with specific online services automatically implies safe usage of the latter is wrong. The only foundation for a safe and responsible usage of online services is being aware of the risks and possessing adequate knowledge on the possible threats. This article discusses the level of knowledge and awareness of the possible threats in using the Internet in students - future teachers.